Rationality in Economics: Theory and Evidence - Sanjit Dhami; Ali al-Nowaihi (Center for Economic Studies and ifo Institute (CESifo), 2018)
We examine the various senses in which economist use the term “rationality” and then outline some of the commonly drawn implications and auxiliary assumptions. Finally, we confront the implications with the empirical evidence, drawing on the insights from the exciting new field of behavioral economics.
Keywords: B40; 330; rationality; self-regarding preferences; efficient markets; heuristics; optimization